2010
DOI: 10.1002/cssc.201000032
|View full text |Cite
|
Sign up to set email alerts
|

The Immobility of CO2 in Marine Sediments Beneath 1500 Meters of Water

Abstract: Injecting liquid CO(2) into deep-sea sediments below ca. 3 km of seawater has been suggested for the permanent storage of anthropogenic CO(2). At the pressures and temperature found below 3 km of seawater, CO(2) becomes denser than seawater and so is likely to remain permanently sequestered in the sediment. Deepwater engineering, however, is expensive and seawater depths of greater than 3 km are often only reached far from shore. Here, we consider the less expensive alternative of injecting CO(2) into marine s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…There is no NBZ for a shallower ocean with depths of 1000 and 2000 m. The decrease of pressure results in lower CO 2 density and lower viscosity, thus leading to higher buoyancy and higher mobility. An increase in mobility can enlarge the footprint of the injected CO 2 ( 21 ), as proven by the smaller distance between the seafloor and the front of the CO 2 plume at the end of the injection ( d PI ) with decreasing ocean depth. Increased buoyancy facilitates the upward flow of CO 2 toward the seafloor, giving rise to the risk of leakage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no NBZ for a shallower ocean with depths of 1000 and 2000 m. The decrease of pressure results in lower CO 2 density and lower viscosity, thus leading to higher buoyancy and higher mobility. An increase in mobility can enlarge the footprint of the injected CO 2 ( 21 ), as proven by the smaller distance between the seafloor and the front of the CO 2 plume at the end of the injection ( d PI ) with decreasing ocean depth. Increased buoyancy facilitates the upward flow of CO 2 toward the seafloor, giving rise to the risk of leakage.…”
Section: Resultsmentioning
confidence: 99%
“…In summary, by systematically studying the coupled process and how the system evolves under complex interactions between phases and components, we investigate the viability of sequestration in deep-sea sediments under different conditions and provide valuable insights into this problem. Compared with previous studies ( 19 , 21 , 24 ), we take different mechanisms into account, including the dynamics of dissolved components and their corresponding effects on hydrate formation and fluid flow, which is the prerequisite for the description of density-driven convection, dissolution of liquid CO 2 and CO 2 hydrate, and diffusion of dissolved CO 2 during the long-term evolution of the system. Because of a lack of consideration of dissolved components, most previous studies are limited to short-term processes.…”
Section: Discussionmentioning
confidence: 99%
“…Liquid was controlled at experimental temperature using the thermostatic bath (3) and registered on a standard thermometer (7) at different points, and the temperatures did not vary more than 0.02 K for about 30 min. Total pressures were recorded on pressure meter (8). The CO 2 concentrations in the gas phase were determined by a CO 2 detector (5).…”
Section: Apparatus and Proceduresmentioning
confidence: 99%
“…[2,3] Presently, many technologies have been developed for the separation and capture of CO 2 , including absorption, [4] adsorption, [5] membrane separation technique, [6] hydrate-based separation process [7] and disposal of CO 2 in deep ocean. [8] Among these technologies, the absorption technology using amine solutions, such as monoethanolamine, [9] diethanolamine, [10] triethanolamine, [11] N-methyldiethanolamine, [12] diglycolamine [13] and EDA, [14] is widely used to capture CO 2 and is considered as the most industrially developed technology for CO 2 absorption. However, the cost of the amine-based absorption processes is relatively high due to the volatilisation of amines, resulting in the consumption of large amounts of energy in the absorption and regeneration processes.…”
Section: Introductionmentioning
confidence: 99%
“…House et al . [] analyzed the long‐term storage of buoyant liquid CO 2 injected into deep‐sea sediments and compared the mobility of liquid CO 2 in marine sediments with that of scCO 2 in geologically equivalent terrestrial reservoirs. They concluded that as long as the pressure and temperature conditions sufficiently yield liquid CO 2 with a density of approximately 90% of seawater, the stored liquid CO 2 is expected to be immobile in deep‐sea formations.…”
Section: Introductionmentioning
confidence: 99%